A paranoia para além da psicose : a manifestação paranoica na ausência de psicose - Braga, Vinícius de Aquino (2016)
Every day we witness scenes of violence, intolerance and conflicts in different ways and intensities, whether on television, in the neighborhood or even inside our homes. Contemporary authors of Psychoanalysis has written about paranoid frames that can manifest even when there is no psychosis. Such frames are related to aggression that we see expressed in various ways. So, our main objective of this work show how you can be a paranoid framework in the absence of psychosis. To do so, we open the job discussing the notion of unconscious structured as a language, situating the field in which we are working and that the subject treated in the course of our exposition. Then, we used a presentation Verwerfung phenomenon to show that, although it is a mechanism usually linked to psychotic structure, is the base of own symbolic order of any speaker. We also demonstrated how the creation of an Ego is properly paranoid to have a rivalitary base that brings into play an aggressiveness (not always) latent, so that we could learn how it leaves marks that can lead a man to present typically paranoid traits, even if can not find a psychosis. This aggression is inherent in the human psyche and constitutes the extent that our Ego - imaginary function - is founded on such a basis where we first know ourselves into the other. Finally, we discuss about what is the paranoia and how manifest paranoid phenomena in order to contribute to a hearing in the clinic in addition to the closure of paranoid runs only in the field of psychosis. We were able to confirm that imaginary phenomena can not be taken alone as a criterion for the structure, and, therefore, we find situations in which paranoid manifestations occur even in the absence of psychosis. As a working method, we conducted literature search, which resorted to reading and rereading of Freud and Lacan, as well as authors who deal with the issue pertaining to the transmission line of these. With this, we aim to raise the concepts in question by promoting a dialogue between them to develop the question presented. The accuracy of the method in psychoanalysis is not in the accumulation of data, but to submit to the laws of language, in order not to us bogged in definitions closed in advance and be able to pay attention to the development of ideas as presented by the authors, as well as the progress the subject who writes.